Search for a light pseudoscalar Higgs boson in the boosted mu mu tau tau final state in proton-proton collisions at root s=13 TeV - CMS Collaboration; Damarseçkin, Serdal (SPRINGER, 2020)
A search for a light pseudoscalar Higgs boson (a) decaying from the 125 GeV (or a heavier) scalar Higgs boson (H) is performed using the 2016 LHC proton-proton collision data at root s = 13 TeV, corresponding to an integrated luminosity of 35.9 fb(-1), collected by the CMS experiment. The analysis considers gluon fusion and vector boson fusion production of the H, followed by the decay H -> aa -> mu mu tau tau, and considers pseudoscalar masses in the range 3.6 < m(a) < 21 GeV. Because of the large mass difference between the H and the a bosons and the small masses of the a boson decay products, both the mu mu and the tau tau pairs have high Lorentz boost and are collimated. The tau tau reconstruction efficiency is increased by modifying the standard technique for hadronic tau lepton decay reconstruction to account for a nearby muon. No significant signal is observed. Model-independent limits are set at 95% confidence level, as a function of m(a), on the branching fraction (B) for H -> aa -> mu mu tau tau, down to 1.5 (2.0)x10(-4) for m(H) = 125 (300) GeV. Model-dependent limits on B(H -> aa) are set within the context of two Higgs doublets plus singlet models, with the most stringent results obtained for Type-III models. These results extend current LHC searches for heavier a bosons that decay to resolved lepton pairs and provide the first such bounds for an H boson with a mass above 125 GeV.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); Higgs physics